A multi-scaled, transdisciplinary study on the impacts and management of Prosopis, one of the world’s worst woody invasive plant taxa - Shackleton, Ross Taylor (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD)--Stellenbosch University, 2016.